Innovative educational standards for Technical education at Slovak primary schools since the school year 2015/2016 - PAVELKA, Jozef (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
This article presents an analysis of possible problems in a school practice that may be caused by the introduction of innovative Technical education at primary schools. The article highlights the need to implement a systematic approach to Technical education and also presents suggestions for possible solutions to be implemented in the near future